2021
DOI: 10.1088/1755-1315/677/2/022004
|View full text |Cite
|
Sign up to set email alerts
|

The development of digital economic in the agricultural sector of region

Abstract: In the national economy of Russia, elements of the digital economy are being actively implemented in various sectors of the economy. With regard to the agricultural sectors, digitalization of production management is an element of strategic development. Insufficiently high rates of development of this direction are accompanied by the influence of various exogenous and endogenous factors in the agricultural sectors of the regional level. The development of public-private partnerships in the agricultural sector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…To ensure stability in the agricultural and food markets in the Altai Krai, measures are being implemented to support the agro-industrial complex and control the level of prices for products [8,9]. The monitoring of the retail trade network of the region showed that agricultural and food products are presented in a fairly wide range, a fairly stable situation with the availability of inventories is noted, there is no shortage of food products [10].…”
Section: Resultsmentioning
confidence: 99%
“…To ensure stability in the agricultural and food markets in the Altai Krai, measures are being implemented to support the agro-industrial complex and control the level of prices for products [8,9]. The monitoring of the retail trade network of the region showed that agricultural and food products are presented in a fairly wide range, a fairly stable situation with the availability of inventories is noted, there is no shortage of food products [10].…”
Section: Resultsmentioning
confidence: 99%
“…Sometimes the authors said about importance the use of elements digital economic. New generation digital technologies have a number of advantages: will increase the efficiency of investments in the agro-industrial complex; «Will become an important element of nonfinancial state support for agriculture» [24].…”
Section: Methodsmentioning
confidence: 99%
“…For many indicators, the target indicators laid down in the Food Security Doctrine have already been achieved. Russia is fully self-sufficient in grain, sugar, poultry and pork [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18. Oilseed export destinations in the Altai Territory (according to Rosselkhoznadzor), % [9,13] Возделывание масличных культур является эффективным направлением развития растениеводства не только с точки зрения выхода на международный рынок, но и как производство органической продукции на маслосемена, спрос на которую неуклонно растет на азиатских рынках [14,15]. Выгодное трансграничное расположение региона, наличие сети автомобильных дорог и железнодорожного транспорта позволяет сельскохозяйственным товаропроизводителям развивать данное направление растениеводства, кроме того, стимулирует развивать переработку масличных культур.…”
Section: рис 3 удельный вес алтайского края в структуре экспорта масл...unclassified